Faktor-Faktor yang Mempengaruhi Perataan Laba pada Perusahaan - Hayatul Millah (Fakultas Ekonomi dan Bisnis Islam, 2015)
Income smoothing is part of the profit management which is management intervention efforts to report on the state of the company that does not reflect the actual situation as there are of particular interest. This is a common phenomenon that is used by management as a way to reduce fluctuations in reported earnings to match the desired target either reduce fluctuations in income reporting, accounting manipulate variables with the selection of accounting methods or by performing real transactions. The income smoothing cause disclosure of information on the net income or profit be misleading, resulting in the occurrence of errors in decision making by parties with an interest in the company, especially external parties. The practice of income smoothing can be detected by several factors such as company size, profitability ratios, operating profit margin, net profit margin and return on assets.